Spending and Growth: A Modified Debt to GDP Dynamic Model - Camilla Yanushevsky; Rafael Yanushevsky (International Journal of Economic Sciences and Applied Research, 2013)
The paper addresses a topical issue – how expansionary fiscal policy affects the debt to GDP ratio. It examines whether the projected future economic growth (stimulated by government spending) is sustained with the resulting national debt. It is discussedif government investment in infrastructure is an effective approach to boost the economy in times of economic downturn. The authors develop the debt to GDP ratio dynamics model and perform a series of simulations (based on US data) to forecast the evolution of the debt to GDP ratio over a 10-year horizon. It is shown that for the data characterizing the current state of the U.S. economy the government investment in infrastructure cannot decrease the debt to GDP ratio.
Keywords: C20; C60; O40; 330; debt dynamics; debt to GDP ratio dynamics; investment in infrastructure; stimulus